Mechanisms and therapeutic targets of mitochondria in the progression of metabolic dysfunction-associated steatotic liver disease - Chenyang Mu; Sijie Wang; Zenghan Wang; Jian Tan; Haozan Yin; Yuefan Wang; Zhihui Dai; Dongyang Ding; Fu Yang (Annals of Hepatology)
Metabolic Dysfunction-Associated Steatotic Liver Disease (MASLD) includes liver disease processes from simple fatty liver to nonalcoholic steatohepatitis, which may progress to liver fibrosis, cirrhosis, and even hepatocellular carcinoma (HCC). As the incidence of HCC derived from viral hepatitis decreases, MASLD has emerged as a significant health threat, driven by lifestyle changes and rising obesity rates among patients. The pathogenesis of MASLD is complex, involving factors such as insulin resistance, gut microbiota imbalance, and genetic and epigenetic factors. In recent years, the role of mitochondrial dysfunction in MASLD has gained significant attention, involving β-oxidation imbalance, oxidative stress increase, mitophagy defects, and mitochondrial DNA (mtDNA) mutations. This article reviews the pathophysiological mechanisms of mitochondrial dysfunction in MASLD, diagnostic methods, and potential therapeutic strategies. By synthesizing current research findings, the review aims to highlight the critical role of mitochondrial dysfunction as a target for future diagnostic and therapeutic interventions. This focus could pave the way for innovative clinical strategies, ultimately improving treatment options and patient prognosis in MASLD.